More than a roof : how can community development help public housing contribute to wellbeing? : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Public Health, SHORE and Whariki Research Centre at Massey University, Auckland, New Zealand - Gallen, Rosie (Massey University, 2025)
Ko ngā kāinga me ngā hapori e noho nei mātau te tūāpapa o te oranga The homes and communities we live in are the foundation of our wellbeing. This thesis explores how community development can enhance the contribution of public housing to resident and community wellbeing in Aotearoa New Zealand. Drawing on qualitative interviews with practitioners and housing professionals across central and local government, the study examines how community development is conceptualised, enacted, and constrained within public housing contexts. Set against a backdrop of institutional transformation—particularly the establishment of Kāinga Ora–Homes and Communities—the research adopts a social constructionist approach to interrogate how trust, care, participation, and organisational culture shape both the practice and potential of community development. Findings reveal that practitioners serve as relational infrastructure: sustaining trust, cultural presence, and collective agency within systems marked by residualisation, policy volatility, and managerial logics. While community development is consistently affirmed at a strategic level, it remains structurally marginalised—underfunded, culturally undervalued, and reliant on the discretionary labour of Māori, Pacific, and women practitioners who bear the emotional and ethical burdens of institutional ambiguity. Despite these constraints, practitioners actively create space for voice, connection, and inclusion—revealing the quiet architecture that holds public housing systems together. Their work is not formally mandated but enacted through presence, care, and cultural fluency. This thesis introduces three conceptual lenses—Creating and Holding Space, The Practitioner as Relational Infrastructure, and Reframing Care as Duty—to propose a grounded model of relational governance. This framework reconceptualises care, trust, and participation not as discretionary virtues, but as core institutional responsibilities. By integrating Indigenous and Pacific relational ontologies with Western theories of care, governance, and participation, the research contributes to an emerging paradigm of public service rooted in equity, accountability, and relational practice. Ultimately, the thesis argues that making public housing more than a roof requires investing not just in buildings, but in people, relationships, and the institutional conditions that allow communities to flourish.
Keywords: community development, public housing, housing renewal, social capital, care, participation, capacity-building, public service, wellbeing; 440707 Housing policy; 330405 Public participation and community engagement